Systematic Transformation and Economic Reforms in Uzbekistan - Islamov, Bakhtior (Mongolian Journal of International Affairs, 2014)
No abstract available DOI: http://dx.doi.org/10.5564/mjia.v0i5.366 The Mongolian Journal of International Affairs; Number 5, 1998, Pages 59-72